Is CHEK2 a moderate-risk breast cancer gene or the younger sister of Li-Fraumeni?. Issue 9 (7th September 2020) - De Silva, Dilanka L; Winship, Ingrid
Abstract : The CHEK2 gene is mostly considered as a moderate breast cancer gene with the result that many clinicians have a narrow focus. We present the 10-year journey of a man who had five different cancers and had iterative genetic testing including for Li-Fraumeni syndrome, eventually to discover a pathogenic variant in the CHEK2 gene, possibly explaining his numerous cancers. This diagnosis offered him closure which he had desperately sought for well over a decade. A pathogenic variant in the CHEK2 gene can potentially explain these cancers because of its function as a tumour suppressor gene. Consideration is warranted of what this means for individuals with CHEK2 variants who may develop multiple cancers, their prognosis and whether different treatment modalities such as chemotherapy, radiotherapy or target agents would need modification. We encourage more research into the many faces of the CHEK2 gene and the potential for predisposition to multiple cancers.